Analisis Yuridis Putusan Niet Ontvankelijke Verklaard Pada Akta Jual Beli - Puspita Wardani, Rila; Iftitah, Anik; Yuliastuti, Eko; Alfaris, Moh.; Widhiandono, Erwin (Jurnal Risalah Hukum, 2024)
This study examines legal certainty in land sale and purchase agreements, particularly concerning sale and purchase deeds that result in Niet Ontvankelijke Verklaard (NO) verdicts. The importance of this study lies in understanding the root causes of legal uncertainty in the transfer of land rights and its implications for the involved parties. The objective of this research is to analyze the causes of NO verdicts, understand their legal basis, and evaluate their legal impacts. The methodology used is a normative legal approach with an analysis of primary and secondary legal materials, as well as related court decisions. The main findings indicate that NO verdicts are caused by unclear dispute objects and formal defects such as error in persona and obscuur libel. NO verdicts impact legal certainty, potential compensation claims, and public trust in notaries/PPATs. The implication is that there is a need to increase meticulousness and compliance with formal requirements in drafting sale and purchase deeds to avoid NO verdicts that can harm various parties.